Melanocytic masses on the tail of three non-grey horses – imaging, histopathology and tail amputation as surgical treatment - Visser, Emi M.S.; Hermans, Hanneke; Veraa, Stefanie; Grinwis, Guy; Ensink, Jos M. (Hippiatrika Verlagsgesellschaf, 2024)
This case series describes three horses presented with masses in the mid and distal tail region. Cytology, histopathology and radiography identified the masses as dermal melanoma and amelanotic melanoma. In all three horses, tail amputation was performed successfully in the standing horse with sedation and an epidural anaesthesia. Two horses diagnosed with an amelanotic melanoma, showed recurrence 2 and 5 months after surgery and were euthanised. The other horse showed no recurrence six months after tail amputation. The horse was performing at previous performance level and showed no complaints of increased insect harassment. This case series describes three non-grey horses with melanocytic masses on the tail, with an amelanotic melanoma carrying a poor prognosis.
Keywords: coccygeal vertebrae; histopathology; horse; melanoma; tumour; Taverne; Equine